“Ridge Sign” to Identify Anterior-Posterior Plane in Small-Incision Lenticule Extraction - Om Parkash T; Om Parkash R; Om Parkash S (Clinical Ophthalmology)
Tushya Om Parkash, Rohit Om Parkash, Sehar Om Parkash Department of Refractive Surgery, Dr Om Parkash Eye Institute, Amritsar, IndiaCorrespondence: Tushya Om Parkash, Email tushya@aol.inPurpose: To describe the “Ridge Sign” as a conclusive indicator for differentiating the anterior and posterior lenticular planes in Small Incision Lenticule Extraction (SMILE).Methods: Femtosecond laser application for SMILE was performed. Anterior and posterior planes were dissected. “Ridge sign” was elucidated prior to proceeding with the final dissection of the anterior plane. Our sign helps to identify anterior and posterior lenticular planes in SMILE. This sign describes a lenticular ridge noted at the junction between the dissected and undissected halves of both planes. This ridge is formed as the lenticule is attached to the cap on one side and to the stromal bed on the other side. Here, the cap is lifted with the blunt dissector’s arm at the junction of the anterior and posterior dissected planes prior to the final dissection of the anterior plane. This maneuver enhances the visibility of the ridge sign and confirms correct initial anterior plane dissection, thereby preventing inadvertent cap lenticular adhesion.Results: In our study, 400 eyes undergoing SMILE procedures using the VisuMax femtosecond laser were included. In 96% of cases, the cap interface was separated first with ridge sign observed in all. In 4% of cases with wrong initial separation of the lenticule interface, the ridge sign was absent. Successful lenticule extraction was achieved in 100% of cases.Conclusion: This confirmatory sign helps to dissect the anterior plane ahead of the posterior plane, thereby ensuring smooth lenticule extraction and preventing inadvertent cap lenticular adhesion, lenticule tears, or partial lenticular dissection.Keywords: SMILE, lenticule dissection, cap lenticular adhesion